2011
DOI: 10.1073/pnas.1114946108
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the de novo DNA methyltransferase Dnmt3a promotes lung tumor progression

Abstract: Alterations in DNA methylation have been associated with genome-wide hypomethylation and regional de novo methylation in numerous cancers. De novo methylation is mediated by the de novo methyltransferases Dnmt3a and 3b, but only Dnmt3b has been implicated in promoting cancer by silencing of tumor-suppressor genes. In this study, we have analyzed the role of Dnmt3a in lung cancer by using a conditional mouse tumor model. We show that Dnmt3a deficiency significantly promotes tumor growth and progression but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
96
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 36 publications
11
96
0
Order By: Relevance
“…It remains unknown whether DNMT3a loss is an oncogenic event; however, it likely plays a central role in genetically diverse cancer cells to proliferate and remain viable under hypoxic conditions. Based on these observations and those of others, we propose that DNMT3a functions as a gatekeeper tumor suppressor (35,36) further genetic studies will be necessary to clearly demonstrate biallelic-inactivating mutations of DNMT3a in primary tumors. Nonetheless, the data shown here underlie the fundamental role of epigenetic reprogramming in the attainment of the hypoxic cancer cell phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains unknown whether DNMT3a loss is an oncogenic event; however, it likely plays a central role in genetically diverse cancer cells to proliferate and remain viable under hypoxic conditions. Based on these observations and those of others, we propose that DNMT3a functions as a gatekeeper tumor suppressor (35,36) further genetic studies will be necessary to clearly demonstrate biallelic-inactivating mutations of DNMT3a in primary tumors. Nonetheless, the data shown here underlie the fundamental role of epigenetic reprogramming in the attainment of the hypoxic cancer cell phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…that DNMT3a is a tumor-suppressor gene and that its mutation, or mRNA down-regulation, contributes to reducing global DNMT3a methyltransferase activity (35,36). Currently, a key challenge is to link aberrant methylation profiles commonly observed in malignant lesions, including alterations in the DNMT3a epigenetic program, to genes that directly promote the tumorigenic phenotype.…”
mentioning
confidence: 99%
“…24,49 To clarify the role of Dnmt3a, Gao et al compared the transcriptome between Dnmt3a-deficient and wild type in mutant K-ras induced mouse lung tumors, and revealed that Dnmt3a was responsible for the maintenance of the methylation-dependent repression of specific oncogenes which were involved in key steps of lung tumor progression, such as angiogenesis, cell adhesion, and cell motion in cancer cells. sequencing to comprehensively characterize the methylomes of wild type and Dnmt3a-deficient mutant K-ras induced mouse lung tumors.…”
Section: The Dual Roles Of Dnmt3a In Cancermentioning
confidence: 99%
“…10 However, several inactivating mutations of DNMT3A in myeloid malignancies [11][12][13][14][15][16][17][18][19][20][21][22][23] and loss of DNMT3A activity at advanced tumor stages 24 were recently identified. In addition, novel roles of DNMT3A in the hematopoiesis system 25 and in the age-related decline of cognition 26 have been revealed.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, it can lead to de-repression of genes promoting cancer progression in certain cancer models. 3,4 Consistent with these observations, recurrent somatic nonsense and missense mutations in DNMT3A have been identified in acute myeloid leukemia (AML) 5,6 and myelodysplastic syndrome. 7 A study by Challen and colleagues reported recently in Nature Genetics 8 utilized conditional Mx-Cre-driven excision to examine the effects of Dnmt3a loss on hematopoietic stem cell (HSC) function.…”
mentioning
confidence: 48%